Investigating the Transepithelial Transport and Enzymatic Stability of Lactononadecapeptide (NIPPLTQTPVVVPPFLQPE), a 19-Amino Acid Casein-Derived Peptide in Caco‑2 Cells - Nakatani, Eriko; Sasai, Masaki; Miyazaki, Hidetoshi; Tanaka, Shimako; Hirota, Tatsuhiko; Okura, Takashi (Journal of Agricultural and Food Chemistry, 2024)
Lactononadecapeptide (LNDP; NIPPLTQTPVVVPPFLQPE), a casein-derived peptide comprising 19 residues, is known for its capacity to enhance cognitive function. This study aimed to explore the transepithelial transport and stability of LNDP. Results showed that LNDP retained over 90% stability after 2 h of treatment with gastrointestinal enzymes. The stability of LNDP on Caco-2 cell monolayers ranged from 93.4% ± 0.9% to 101.1% ± 1.2% over a period of 15–60 min, with no significant differences at each time point. The permeability of LNDP across an artificial lipid membrane was very low with the effective permeability of 3.6 × 10–11 cm/s. The Caco-2 assay demonstrated that LNDP could traverse the intestinal epithelium, with an apparent permeability of 1.22 × 10–6 cm/s. Its transport was significantly inhibited to 67.9% ± 5.0% of the control by Gly-Pro, a competitor of peptide transporter 1 (PEPT1). Furthermore, PEPT1 knockdown using siRNA significantly inhibited LNDP transport by 77.6% ± 1.9% in Caco-2 cell monolayers. The LNDP uptake in PEPT1-expressing HEK293 cells was significantly higher (54.5% ± 14.6%) than that in mock cells. These findings suggest that PEPT1 plays a crucial role in LNDP transport, and LNDP exhibits good resistance to gastrointestinal enzymes.